Penerapan Knowledge Management sebagai Budaya Organisasi - Kusmaningtyas, Amiartuti (Kajian Manajemen dan Bisnis, 2010)
ASEAN-China Free Trade Area (ACFTA), which took effect since January 1, 2010 cannot directly stimulate corporate creativity and productivity. Efforts can be made related to the human resource conditions in Indonesia to increase the capacity and capability of the workforce. This can be achieved through the company's ability to manage knowledge (Knowledge Management) owned by individuals and make it as a corporate culture. Knowledge Management which has been embedded in the corporate culture is a good quality solution for organizations (companies) to compete in the market.